Localization of DER and the pattern of cell divisions in wild-type and Ellipse eye imaginal discs. - Zak, N.B.; Shilo, B.Z. (Developmental Biology, 1992)
The compound eye of Drosophila develops from a uniform layer of epithelial cells in the eye imaginal disc. One intriguing aspect of eye development is the establishment of the correct number and spacing of the photoreceptor clusters which give rise to the mature ommatidia. Ellipse (Elp) has been implicated as playing a role in this process because the Elp dominant gain of function mutation dramatically reduces the number of photoreceptor clusters in the compound eye without affecting the morphology of individual clusters that are formed (Baker and Rubin, 1989). Since Elp represents an allele of the Drosophila EGF receptor (DER) locus, it encodes a protein which is structurally capable of mediating inductive cell-cell interactions. In an effort to better understand the role of the DER locus in ommatidial patterning, we compared the localization of DER protein in eye imaginal discs of wild-type and Elp larvae. The distribution of this receptor is consistent with the notion of its mediating interactions between cells at the initial stages of photoreceptor precluster positioning and differentiation. However, the basis of the Elp gain of function mutation is not ectopic or increased expression of the DER protein. Rather, expression of the Elp form of the EGF receptor homolog in the normal localization leads to changes in the proliferative pattern of cells dividing posterior to the morphogenetic furrow.